The Compatibility of Iraqi Legislation with the Requirements of the International Financial System in Financing Foreign Trade A Legal Study on the Technical Challenges of Payment Systems and Electronic Payment Methods - Saadi, Farhad; Murad, Khairi (Journal of Legal Sciences, 2023)
The research examines the current Iraqi legislation regarding financing of its foreign trade, its mechanism, and the methods used for money transfers. The research aim is to determine the extent to which these legislations comply with the requirements of the international financial system and identify any legislative shortcomings that negatively affect the value of the national currency, facilitate money laundering, and pose risks to the Iraqi economy and the international financial system simultaneously.The current reality of financing foreign trade and the mechanism of the foreign currency sale window used by the Central Bank do not constitute genuine financing and have introduced risks, such as money laundering. The Central Bank, by combining the control mechanism over financial transfers and the practice of monetary policy to stabilize the exchange rate of the national currency, has burdened itself with additional responsibilities and hindered the proper implementation of its monetary policy. Studies confirm that genuine financing occurs through specific credit-based payment methods and an effective monitoring is achieved by distributing the control over payment instruments and money transfers among relevant parties. The electronic payment system and the tools introduced by the Central Bank do not adequately accommodate the amounts and guarantees required by traders themselves in international trade contracts. Compared to more suitable payment methods for financing and money transfers, such as commercial remittances -Bill of Exchange- and letter of credits, the Central Bank has not assigned sufficient importance to credit facilities, and attract traders to use suitable methods as payment instruments in international trade, avoiding the complications of paper-based forms. Consequently, the impact of Iraq's legislation's failure to keep pace with technological and legal developments in the field of commercial transactions on the Iraqi economy has been observed, emphasizing the need to propose effective solutions to enhance Iraqi legislation in this context.